Ferroptosis is involved in the benzene-induced hematotoxicity in mice via iron metabolism, oxidative stress and NRF2 signaling pathway. (1st August 2022) - Sun, Rongli; Liu, Manman; Xu, Kai; Pu, Yunqiu; Huang, Jiawei; Liu, Jinyan; Zhang, Juan; Yin, Lihong; Pu, Yuepu
Abstract: Benzene is a pollutant that widely exists in the environment and in occupational workplaces. Its exposure is closely associated with hematological disorders and even leukemia, which poses a significant threat to public health. Thus, the underlying mechanisms should be explored. In the current study, it was investigated whether ferroptosis plays a role in benzene hematopoietic toxicity and related mechanisms. Mice were subcutaneously injected with benzene at 150 mg/kg b.w. to establish a hematotoxicity model. Four weeks later, the mice exposed to benzene exhibited a decrease in white blood cells, red blood cells, and hemoglobin level, as well as reduction in frequency of hematopoietic stem and progenitor cells (HS/PCs) and the colony forming abilities of CFU-G, CFU-M, CFU-GM, and CFU-GEMM. Simultaneously, apart from ferroptosis features in the mitochondrial morphology, decreased ATP and mitochondrial membrane potential, alterations in biochemical indices and gene expression were also observed, such as increased intracellular iron and lipid peroxidation, glutathione (GSH) depletion, and reduced glutathione peroxidase (GSH-Px) level, and upregulated PTGS2. Meanwhile, markedly altered expression of SLC7A11, GPX4, GCLC, NOX1, TFRC, FTH1, and FTL hinted that redox imbalance and dysfunction of iron uptake and storage are vital to induce ferroptosis. Additionally, decreased cytoplasmic NRF2 and increased nuclear NRF2 were also found, suggesting the activation of the NRF2 pathway. More importantly, inhibition of ferroptosis with ferrostatin-1 (Fer-1) or deferoxamine (DFO) partially relieved the hematopoietic injuries. Our findings imply that dysregulation in the system Xc − /GPX4 axis, iron metabolism, and activation of the NRF2 pathway play a crucial role in benzene-induced ferroptosis, and reveals that taking ferroptosis as a target may be a potential intervention strategy for benzene-induced hematotoxicity. Highlights: Benzene induced ferroptosis through iron overload and dysfunction of iron metabolism. Benzene disturbed redox homeostasis and system Xc − /GPX4 during ferroptosis. Inhibition of ferroptosis could partially relieve benzene-caused hematotoxicity.